Principles of cash flow valuation an integrated market-based approach - Tham, Joseph; Velez Pareja, Ignacio, 1943- (Amsterdam ; Boston, MA : Elsevier Academic Press, 2004)
The valuation of assets, both tangible and intangible, is an important element of corporate finance. Putting a price tag on ideas is almost impossible, and in the new economy, where companies grow dependent on intangible assets all the time, market volatility can be attributed in large part to our collective ignorance of their value. There are two basic approaches to valuation: from financial statements to cash flows, and from cash flows to financial statements. The former projects historical financial statements into the future and the latter attempts to construct cash flow statements and use them in forecasting future financial statements. Established companies use the first method and start-ups the second. In Principles of Cash Flow Valuation, the authors strive to "close the gap" between these two approaches by presenting the principles of cash flow valuation and cost of capital in a clear and systematic fashion. * Provides the only exclusive treatment of cash flow valuation * Authors use examples and a case study to illustrate ideas * Presentation appropriate for a range of technical backgrounds: ideas are presented clearly, full exposition is also provided * Named among the Top 10 financial engineering titles by Financial Engineering News.
Basic concepts in market-based cash flow valuation; Time value of money (TVM) and introduction to cost of capital; Basic review of financial statements and accounting concepts; Constructing integrated pro-forma financial statements; Derivation of the free cash flows; Using the WACC in theory and in practice; Estimating the WACC for non traded firms; Beyond the planning period: calculating the terminal value; Theory for cost of capital revisited;How are Cash Flows Valued in Reality?
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Cash flow -- Valuation; Cash flow -- Accounting; Electronic books